KESELAMATAN KERJA PADA AKTIVITAS DI AREA DOCKING KAPAL PT PERIKANAN INDONESIA MUARA BARU - Fis Purwangka; Ignatius Viktor Deornay; Prihatin Ika Wahyuningrum (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
As a company with a high potential for work accidents, the dockyard owned by PT Perikanan Indonesia must create a safe working environment for its workers by implementing occupationalsafety and health. However, until now, the company does not have a complete Standard OperatingProcedure (SOP) that meets labor safety standards. To improve and complete the SOP under worksafety standards, it is necessary to identify the behavior of the workforce and potential hazards inevery docking activity that can harm workers or the company. The purpose of this study is to identifyactivities that are potentially hazardous to workers in the docking area. The method used isdescriptive analysis and the method of Job Safety Analysis (JSA). The results of the study indicatethat extreme risk level is present when the vessel's activity enters the docking area, associated withthe vessel's hull on the rail slipway, vessel towing, vessel brushing, and vessel caulking.. This is dueto the dangerous behavior and dangerous conditions of the observations during the study. Keywords: docking, job incidents, job safety, job safety analysis, shipyard.